Restructuring Traditional Merit Making: The Moral Economy of Contemporary Peasant Society and The Transformation of Post Peasant Society in Isan Rurban Area, A Case Study of Baan Sri-Kai Ok, Amphoe Warin Chamrap, Ubon Ratchathani Province - Pocapanishwong, Nattchawal (Journal of Social Sciences Naresuan University, 2020)
This research article intends to understand the dynamics of peasant society through the re-structuring of a traditional culture in a community of northeastern Thailand, Baan Sri-Kai Ok, Amphoe Warin Chamrap, Ubon Ratchathani Province. This study uses a qualitative research method. The researcher found that the community tries to maintain the potential for self-reliance by using a traditional merit making as a tool. The practice focuses on two principles: “rational subsistence security” and “balancing moral obligation” which differ from the norm of reciprocity in the patronage system. This practice is characteristic of the moral economy in contemporary peasant society. On the other hand, the community has transformed into a post peasant society that combines urban and rural, polybius identity, and raising the socio-economic status of the rurban villagers.